Observational study of adjuvant therapy with capecitabine in colon cancer. (12th February 2015) - Steffens, Claus-Christoph; Tschechne, Barbara; Schardt, Christof; Jacobs, Georg; Valdix, Annette-Rosel; Schmidt, Peter; Hansen, Richard; Kröning, Hendrik; Wohlfarth, Tim; Guggenberger, Dorothee
Abstract: Objective: This observational study was conducted to document the safety of capecitabine-based adjuvant therapy in patients with resected colon cancer under routine clinical conditions. Research and design methods: ML20431 was a prospective, multicenter, non-interventional, observational study. It was designed to answer five research questions relating to safety, dosage and administration, and discontinuation from capecitabine-based adjuvant therapy. Patients were required to have R0 resected stage III colon cancer and have started treatment with capecitabine-based adjuvant therapy based on a decision by the investigator. Patients were followed over an observation period of ≤6 months after initiation of therapy. Investigators were required to complete the study case report form at study entry, each treatment cycle, and at the final examination. Main outcome measures: A total of 1485 patients were included in the study, and 1481 patients were treated with capecitabine and formed the analysis population. Most patients had colon cancer (78.3%), followed by rectal cancer (16.4%). Most patients had stage III disease (69.3%); the remaining patients had stage II disease (30.7%). The most common all-grade adverse reactions were hand–foot syndrome (46.9%), diarrhea (34.4%), and hemoglobin decreases (31.5%). Grade 3/4 adverse reactions were infrequent (<4%). Serious adverse events were reported in 96 patients (6.5%). Six or more cycles of treatment were completed by 77.9% of patients. Approximately two-thirds of patients (67.3%) received capecitabine monotherapy and the remainder (32.7%) received capecitabine in combination with ≥1 drugs, most commonly oxaliplatin (460 cases). Discontinuation of capecitabine was documented in 344 patients (23.2%). Study limitations: no efficacy data were collected; the questionnaires for patients' expectations and satisfaction were not formally validated; and a few patients (<1.5%) had some retrospective data. Conclusions: The safety profile of capecitabine-based adjuvant therapy in a broad patient population with colon cancer is similar to that previously documented in phase III clinical trials.